Attendance at day care centers increases the risk of childhood pneumonia among the urban poor in Fortaleza, Brazil - Fonseca Walter; Kirkwood Betty R.; Barros Aluisio J. D.; Misago Chizuru; Correia Luciano L.; Flores Jose A. M.; Fuchs Sandra C.; Victora Cesar G. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1996)
We carried out a case-control study to investigate risk factors for childhood pneumonia in two groups of 650 children aged under two years in the city of Fortaleza, Ceará, Brazil. The cases were children recruited at the main pediatric hospital with a radiological diagnosis of pneumonia, and controls were children of the same age group recruited from the neighbourhood of the cases. In this paper we focus on variables related to childcare practices. Working mothers, proportion of time the mother had worked since the child was born, and use of day care centers emerged as important risk factors with estimated relative risks of 1.58, 1.76 and 5.22, respectively. Also important were the number of children living in the house and presence of grandparents. However, the presence of siblings under two years and the birth order were not associated with pneumonia. All analysis included adjustment for confounding by income, parents' education, and other risk factors as appropriate. This is the first study from a developing country to identify attendance at day care centers as a risk factor for increased childhood morbidity, in this case pneumonia. This finding is of significant public health importance for countries such as Brazil with growing urban populations and an increasing need by mothers to find work outside the home.